The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1097/lgt.0000000000000428
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Adenoid Basal Carcinoma: Clinicopathologic Features of 9 Cases With Reference to CK17 and Ki-67 Expression

Abstract: Adenoid basal carcinoma had characteristic morphological features, and the differential diagnosis of ABC from SCC is usually simple, based on morphology. In select cases, when histological findings are equivocal, the loss of CK17 expression in the squamous differentiation area, and a lower Ki-67 index in basal cell foci support ABC diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Ferry et al reported a distinct age distribution among patients with ACC and ABC, and most cases occurred in Western countries (19). Early reports indicated that the median age of postmenopausal black women with cervical ACC and ABC was mainly between the 60s and 70s (range, 50-86 years) (12,17,18,21). Consistent with previous findings, the data of our study demonstrated that the median age of cervical ACC and ABC patients was 70 years (range, 62-78 years).…”
Section: Analysis For Radiotherapy or Chemotherapy Patientsmentioning
confidence: 99%
“…Ferry et al reported a distinct age distribution among patients with ACC and ABC, and most cases occurred in Western countries (19). Early reports indicated that the median age of postmenopausal black women with cervical ACC and ABC was mainly between the 60s and 70s (range, 50-86 years) (12,17,18,21). Consistent with previous findings, the data of our study demonstrated that the median age of cervical ACC and ABC patients was 70 years (range, 62-78 years).…”
Section: Analysis For Radiotherapy or Chemotherapy Patientsmentioning
confidence: 99%
“…CABCC was rst reported in 1966 and primarily occurs in postmenopausal women accompanied with other pathological type of cervical carcinoma. The levels of carbohydrate antigen 125, squamous cell carcinoma antigen and carbohydrate antigen 199 in serum are mostly within the normal range (3). For individuals who develop this disease, they may experience abnormal vaginal bleeding or contact bleeding, and the cervix may exhibit an obvious mass as it is basically accompanied by other types of cancer (4).…”
Section: Introductionmentioning
confidence: 99%